Regulatory T Cells Accumulate and Proliferate in the Ischemic Hemisphere for up to 30 Days after MCAO. Issue 1 (January 2013) - Stubbe, Tobias; Ebner, Friederike; Richter, Daniel; Engel, Odilo Randolf; Klehmet, Juliane; Royl, Georg; Meisel, Andreas; Nitsch, Robert; Meisel, Christian; Brandt, Christine
Local and peripheral immune responses are activated after ischemic stroke. In our present study, we investigated the temporal distribution, location, induction, and function of regulatory T cells (Tregs) and the possible involvement of microglia, macrophages, and dendritic cells after middle cerebral artery occlusion (MCAO). C57BL/6J and Foxp3 EGFP transgenic mice were subjected to 30 minutes MCAO. On days 7, 14, and 30 after MCAO, Tregs and antigen presenting cells were analyzed using fluorescence activated cell sorting multicolor staining and immunohistochemistry. A strong accumulation of Tregs was observed on days 14 and 30 in the ischemic hemisphere accompanied by the elevated presence and activation of microglia. Dendritic cells and macrophages were found on each analyzed day. About 60% of Foxp3 + Tregs in ischemic hemispheres were positive for the proliferation marker Ki-67 on days 7 and 14 after MCAO. The transfer of naive CD4 + cells depleted of Foxp3 + Tregs into RAG1 −/– mice 1 day before MCAO did not lead to a de novo generation of Tregs 14 days after surgery. After depletion of CD25 + Tregs, no changes regarding neurologic outcome were detected. The sustained presence of Tregs in the brain after MCAO indicates a long-lasting immunological alteration and involvement of brain cells in immunoregulatory mechanisms.